2004
DOI: 10.1158/1541-7786.141.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenetic Protein-2 Stimulates Angiogenesis in Developing Tumors

Abstract: Bone Morphogenetic Protein-2 (BMP-2) is highly overexpressed in the majority of patient-derived lung carcinomas. However, a mechanism revealing its role in cancer has not been established. Here we report that BMP-2 enhances the neovascularization of developing tumors. Recombinant BMP-2 stimulated blood vessel formation in tumors formed from A549 cells injected s.c. into thymic nude mice. Recombinant BMP-2 also enhanced angiogenesis in Matrigel plugs containing A549 cells in nude mice. The BMP-2 antagonist nogg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 246 publications
(35 citation statements)
references
References 45 publications
1
34
0
Order By: Relevance
“…Investigations into this area have proceeded in varying degrees in both in vitro and in vivo studies, which have revealed discordant findings based on the tumor site, tumor type, and BMP studied. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Most BMP-based bone tissue engineering approaches use a BMP-2 platform, either with protein or gene therapy. Previously reported data have shown that BMP-2 and the receptor BMPR-IA were frequently expressed in human tumors as detected by immunohistochemistry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations into this area have proceeded in varying degrees in both in vitro and in vivo studies, which have revealed discordant findings based on the tumor site, tumor type, and BMP studied. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Most BMP-based bone tissue engineering approaches use a BMP-2 platform, either with protein or gene therapy. Previously reported data have shown that BMP-2 and the receptor BMPR-IA were frequently expressed in human tumors as detected by immunohistochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…The potential role of BMPs in malignant transformation and cancer progression remains poorly understood. Investigations into this area have proceeded in varying degrees in both in vitro and in vivo studies, which have revealed discordant findings based on the tumor site, tumor type, and BMP studied 19‐35 . Most BMP‐based bone tissue engineering approaches use a BMP‐2 platform, either with protein or gene therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Small molecule inhibitors of BMP signaling decrease growth and survival of cancer cells in vitro and in mouse tumor xenografts 38 . Mechanistically BMP signaling cascade regulates several important survival pathways in cancer cells including the activation PI3K 39 41 , increasing expression of anti-apoptotic proteins 42 45 , increase expression of inhibitor of differentiation proteins (Id1-4) 46 , 47 , and by promoting tumor angiogenesis 48 . Furthermore, BMP inhibition destabilizes microtubules, which enhances lysosome activity and when combined with Ym155 increases lysosome permeability 15 .…”
Section: Discussionmentioning
confidence: 99%
“…20 In developing tumors, both Smad1/5 phosphorylation and its subsequent nuclear translocation induced by BMP-2 were observed in endothelial cells and played important roles in tumor angiogenesis. 21 Although there is still a dispute on the exact role of the Smad1/5 phosphorylation pathway in the function of endothelial cells, many experts still believe that Smad1/5 phosphorylation inhibits proliferation, migration, adhesion, and spread of endothelial cells. 22,23 Here, we presented evidence that Erbin knockdown-induced Smad1/5 phosphorylation and that nuclear translocation impairs endothelial cell migration and tubular structure formation.…”
Section: Discussionmentioning
confidence: 99%